Treating People With Epilepsy in Rural Low-Income Countries Is Feasible. Observations and Reflections From a “Real Life Experience” After a Long Lasting Intervention in the Rural Chaco - Nicoletti, Alessandra; Giuliano, Loretta; Colli, Chiara; Cicero, Calogero Edoardo; Padilla, Sandra; Vilte, Estela; Rojo Mayaregua, David; Martinez, Maria Del Carmen; Camargo, Mario; Zappia, Mario; Bartoloni, Alessandro; Crespo Gómez, Elizabeth Blanca (Frontiers in Neurology, 2018)
Introduction: Epilepsy represents an important public health issue, in particular in low and middle-income countries where significant disparities are present in the care available for patients with epilepsy. Treatment cost and unavailability of drugs represent important barriers in treating people with epilepsy especially in rural setting. Aim of the study was to evaluate, by means of routine data, the current real-life clinical practice in epilepsy in the rural communities of the Plurinational State of Bolivia. Treatment activity followed educational campaigns and an anthropological fieldwork over more than 20 years. Material and methods: Medical records of people with epilepsy (PWE) living in the rural communities of the Bolivian Chaco who received antiepileptic drugs (AEDs), from 2012 to 2016, and were followed-up for at least 1 year were analysed. Treatment delivery and follow up visits were managed by a neurologist with the support of rural health care workers. Results: From 2012 to 2016, 157 PWE (76 men with a mean age of 24.2 ± 15.7) have been included in the study. Structural epilepsy was the most common type, recorded in 54 cases (34.4%) and the most common reported causes were perinatal factors, present in 11 subjects (20.0%). Almost all patients presented epilepsy with generalized tonic-clonic seizures (91.4%). The most common AED prescribed was phenobarbital followed by carbamazepine. During the follow-up, a dramatic seizures reduction was observed, with 31 subjects (29.2%) being seizures-free at the last follow-up. However, 48 subjects (30.6%) did not assume the medication regularly and 10 interrupted the drug intake. More than 20% of PWE did not receive any financial supports for AEDs. During the follow-up period 10 patients died but only in one case the death was probably caused by epilepsy. Conclusion: Our study demonstrated that PWE in rural areas of the Bolivian Chaco are willing to seek medical attention and to receive antiepileptic treatment. However, improvement in care is needed to assure compliance to AED treatment, including activity to increase awareness towards epilepsy among community members and health staff of the rural communities and to guarantee the coverage of treatment costs and drug supply.